How to Build Loyalty: The Role of Customer Satisfaction Gopay E-Wallet - Alya Takwarina Cahyani; I Made Bayu Dirgantara (Fokus Ekonomi : Jurnal Ilmiah Ekonomi, 2022)
The purpose of this research is to test and analyze the influence of experience and digital services quality to the satisfaction and its impact on customer loyalty of e-wallet Gopay di Semarang. A total sample of 110 respondents, the sampling technique used in this research is purposive sampling, purposive indicates that the data are taken from a specific target. The findings revealed that customer satisfaction is positively influenced by experience and digital service quality; customer loyalty is positively influenced by experience and digital service quality, and subsequent satisfaction influences customer loyalty of e-wallet Gopay. Satisfaction has the ability to mediate the impact of customer experience variables on customer loyalty, as well as the impact of varying digital service quality on customer loyalty in the e-wallet Gopay.